Resolving Late Consequences of Prenatal Stress with Dynamic Tandem Hypnotherapy (DTH) (Global Journal of Medical Research, 2020)
Dynamic Tandem Hypnotherapy (DTH) was evolved more than ten years ago by the authors. It designates a kind of group-hypnotherapy, which is used for resolving late pathological consequences of prenatal traumas. In tandem hypnotherapy sessions more than two persons take part in: the patient and the co-therapist, who touch each other and go into a trance together; while the hypnotherapist keeps the distance. A mutual attunement is developed between the participants being in a tandem trance, which seems as serving for the therapeutic effect. Touch is considered as having the possibility to create calm, safety, and love, which are viewed to be lost or confined by unbearable emotions of prenatal traumas. Moreover, touch is viewed as the mother of perceptions, the "skin-ego," which already functions when there is no central nervous system developed yet. Thus consequences of prenatal stress can be healed with such a therapeutic approach at the same functional level on which the trauma occurred. Four case vignettes will be shown with interpretations upon how DTH works.
Keywords: dynamic tandem hypnotherapy; prenatal stress; fetal consciousness; healing effects of DTH